2006
DOI: 10.1681/asn.2006030194
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis

Abstract: Peritoneal membrane solute transport in peritoneal dialysis (PD) patients is assessed by the peritoneal equilibration test, which measures the ratio of creatinine in the dialysate to plasma after a standardized 4-h dwell (D/P c ). Patients then are classified as high, high-average, low-average, or low transporters on the basis of this result. A meta-analysis of observational studies was carried out to characterize the relationship between D/P c and mortality and technique failure in patients who are on PD. Cit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
202
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(221 citation statements)
references
References 40 publications
14
202
2
1
Order By: Relevance
“…Peritoneal membrane function is an independent predictor of patient survival, with those with high transporter status and, therefore, decreased ultrafiltration capacity demonstrating worse outcomes [26]. In a metaanalysis Brimble et al showed an increased mortality risk of 21.9%, 45.7%, and 77.3% in low-average, high-average and high transporters, respectively, compared with patients with low transporter status [27].…”
Section: Peritoneal Dialysis Access and Preservation Of Membrane Funcmentioning
confidence: 99%
“…Peritoneal membrane function is an independent predictor of patient survival, with those with high transporter status and, therefore, decreased ultrafiltration capacity demonstrating worse outcomes [26]. In a metaanalysis Brimble et al showed an increased mortality risk of 21.9%, 45.7%, and 77.3% in low-average, high-average and high transporters, respectively, compared with patients with low transporter status [27].…”
Section: Peritoneal Dialysis Access and Preservation Of Membrane Funcmentioning
confidence: 99%
“…It may be present at the initiation of peritoneal dialysis (PD) but may develop with time on treatment (2,3). Studies of continuous ambulatory PD (CAPD) patients have demonstrated baseline fPTS to be an independent predictor of mortality and technique failure (4). Explanations for this association include reduced peritoneal membrane ultrafiltration capacity owing to more rapid dissipation of the glucose osmotic gradient and resultant fluid reabsorption (5).…”
mentioning
confidence: 99%
“…Patients who are fast transporters have been shown to have evidence of intraperitoneal inflammation (12) and do less well on continuous ambulatory peritoneal dialysis (CAPD) (13). PD prescriptions for this group use APD to deliver shorter dwell times as well as higher dialysate glucose concentrations to avoid reabsorption of fluid.…”
Section: Evaluating Peritoneal Membrane Functionmentioning
confidence: 99%